From Procurement to Consumption: A Model to Understand Nutrition Policy Implementation in Permanent Supportive Housing - Rebekah J. Russell; Briana McIntosh; Nicole R. Palmer; Morgan Taggart; Erika Trapl (Ohio Journal of Public Health, 2022)
Background: Food insecurity has become an increasingly complex public health issue across the United States, particularly among various people battling with current or previous homelessness. This project sought to understand the food system in permanent supportive housing sites (PSH) that serve formerly homeless individuals and to explore the use of nutrition standards, specifically the Food Service Guidelines for Federal Facilities (FSGFFs), in this context. Methods: Participants were members of the administrative staff involved in the food procurement process, food preparation, administrative tasks, and daily operations in a small-intensive program managed by a local nonprofit agency that serves 12 adults over the age of 18 who experience chronic homelessness and persistent mental illness, or substance use disorders, and a second PSH site that helps 41 low-income adults with health conditions experiencing homelessness. The PSH Inquiry Tool (PSH-IT) was developed to better understand the business operations at each site, and the PSH Audit (PSH-A) was created to assess the applicability of FSGFF at each site. Results: Findings suggest that funding mechanisms, staff training, staff capacity, and access to nutrition education were critical barriers to the successful development and implementation of nutrition standards in PSH sites. Furthermore, findings suggest that adaptations to FSGFFs are required before implementation at PSH sites. Conclusion: This report advocates for increased involvement of community stakeholders to support nutrition policy development and implementation, a nutrition policy that impacts all levels of the food system from procurement to consumption, and local, state, or federal policy changes to support improved nutrition in PSH.
Keywords: Homelessness; Food insecurity; Permanent supportive housing; Nutrition policy; Case study